(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2011)
Performance measurement is considered one of the most important issues in Measuring performance effectiveness in the educational institutions by maintaining balance among quantity measurable factors. They can be financial or non‐financial factors. Consequently they reflect decisive factors in the success of educational institutions and determining suitable standards and dimensions for their activities and giving it proportional importance. Adopting the idea of Balanced Score Card as one of the modern administrative techniques and methods by educational institutions assists in the development of administrative work, adjusting the performance in addition to achieving comprehensive standard and development of educational universities under scarcity of resources and competition of activities to gain as much as possible. This need increases academically to develop this standard in the aim at portioning allocated resources during application.